1974
DOI: 10.1017/s0047404500004358
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic change and diffusion: description and explanation in sociolinguistic dialect geography

Abstract: Linguistic geography has remained relatively unaffected by recent developments in sociolinguistic theory and method and theoretical geography. In this paper it is argued that insights and techniques from both these disciplines will be of value in improving descriptions of geographical variation in language, and that these improvements will in turn lead to more adequate explanations for certain of the social and spatial characteristics of linguistic change. Evidence in favour of a sociolinguistic methodology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
1
15

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(247 citation statements)
references
References 10 publications
9
222
1
15
Order By: Relevance
“…One of the most significant findings to emerge from this study is that /l/-vocalization, having contra-hierarchically spread from rural Emmental to urban Bern and establishing itself robustly within the Bernese "cultural hearth," is now spreading further in a wavelike fashion, particularly to the southwest, the south, and the southeast of German-speaking Switzerland, while appearing to be absent in the Northern Plateau. It was also shown that the degree of vocalization is contingent on the phonological context, which in turn interacts with the specific location under investigation, as Trudgill (1986) and Labov (2007) predicted in cases of dialect diffusion. The findings further suggest an effect for age on the degree of vocalization, with older people tending to vocalize more than younger people do, especially in central Switzerland.…”
Section: O N C L U S I O N S a N D O U T L O O Kmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the most significant findings to emerge from this study is that /l/-vocalization, having contra-hierarchically spread from rural Emmental to urban Bern and establishing itself robustly within the Bernese "cultural hearth," is now spreading further in a wavelike fashion, particularly to the southwest, the south, and the southeast of German-speaking Switzerland, while appearing to be absent in the Northern Plateau. It was also shown that the degree of vocalization is contingent on the phonological context, which in turn interacts with the specific location under investigation, as Trudgill (1986) and Labov (2007) predicted in cases of dialect diffusion. The findings further suggest an effect for age on the degree of vocalization, with older people tending to vocalize more than younger people do, especially in central Switzerland.…”
Section: O N C L U S I O N S a N D O U T L O O Kmentioning
confidence: 94%
“…It has long been noted that diffusing linguistic innovations morph as they spread (e.g., Britain, 2005Britain, , 2010Trudgill, 1986): (i) socially, by being differently sociologically embedded in the destination from in the source (witness, for example, the diffusion of the glottalization of /t/ from the Southeast of England, where it tends to be used most in informal styles and among working-class speakers, to Cardiff in Wales, where highest rates are found among middle-class women in more formal speech styles) (Mees & Collins, 1999); (ii) attitudinally, through evolutions in how innovations are evaluated; and (iii), importantly, linguistically, as innovations embed themselves into local grammars that often differ from one place to another. Labov (2007) showed how the diffusion of the complex New York system of short /a/ tensing to Northern New Jersey, Albany, Cincinnati, and New Orleans has led to subtle yet significant and, what is more, different changes in each.…”
Section: Vocalization By Phonological Context and Locationmentioning
confidence: 99%
“…The other chapters in this section (by Britten on diffusion and Kerswill on koineization) deal with contact among speech varieties that are more closely related. However, some of the same processes involved in these cases will also be seen to operate across language boundaries -the diffusion of uvular (r) in a number of European languages is one well-known example (Trudgill 1974a; see also Tristram 1995).…”
Section: Introductionmentioning
confidence: 99%
“…опубликовано 133 статьи (т. [11][12][13][14][15][16][17][18][19][20]; из них 61, чуть менее 46%, касались исключительно фонетических тем, и многие другие включали фонети-ческие переменные в число других или использовали их в качестве основных при определении вариации других переменных, в первую очередь морфологических [18, р. 189].…”
Section: социофонетическое направление в зарубежной лингвистикеunclassified
“…Важным шагом на пути к пониманию понятия «диффузия» стало исследование П. Традгилла (1973), проведенное на полуострове Брунланес Норуэя. В гравитационной модели диффузии П. Традгилла измене-ние распространяется от крупнейших городов до следующего крупного города, в предсказуемом порядке, влияние одного города на другой пропорционально отношению размеров города и обратно пропорциональ-но расстоянию между ними [20].…”
Section: социофонетическое направление в зарубежной лингвистикеunclassified